Why Should Organizational Scholars Study Migration? - Hernandez, Exequiel; Choudhury, Prithwiraj; Kulchina, Elena; Wang, Dan; Shaver, J. Myles; Zellmer-Bruhn, Mary; Khanna, Tarun (Organization Science, 2025)
Migration is one of the most significant forces shaping economies and societies, yet it remains largely understudied in organizational research. At the same time, scholars in other fields with long traditions of studying migration tend to overlook the essential role of organizations. This lack of dialogue is striking because organizations are often the central arena in which migrants interact with others and through which they impact society and the economy. We explain how scholars of migration and organizations can benefit each other by exploring two broad issues. First, we consider what an organizational lens can add to the existing migration literature. We argue that organizational heterogeneity plays an essential role in determining the causes and effects of migration. Second, we consider how taking migration seriously can yield theoretical advancements for organizational scholars. We present examples that introduce potentially novel theoretical concepts or that enrich existing theories. Our aim is to broaden the research agenda for scholars interested in migration or organizations and to motivate organizational scholars to engage more deeply with one of the most consequential issues of our time. History: This paper has been accepted for the Organization Science Special Issue on Migration & Organizations.